The Impact of Maternal High-Fat Diet on Bone Microarchitecture in Offspring - Buckels, Emma J.; Bolam, Scott M.; Tay, Mei Lin; Matthews, Brya G. (Frontiers in Nutrition, 2021)
The incidence of obesity in women of reproductive age has significantly increased over the past 100 years. There is a well-established connection between maternal obesity during pregnancy and an increased risk of developing non-communicable cardiometabolic diseases in her offspring. This mini-review focuses on evidence examining the effect of maternal high-fat diet (HFD) on skeletal development and bone health in later life in offspring. The majority of rodent studies indicate that maternal HFD generally negatively affects both embryonic bone development and bone volume in adult animals. Details surrounding the mechanisms of action that drive changes in the skeleton in offspring remain unclear, although numerous studies suggest that some effects are sex-specific. Human studies in this area are limited but also suggest that HFD during pregnancy may impair bone formation and increase fracture risk during childhood. Given the consequences of low bone mass and deranged bone microarchitecture for offspring, advances in our understanding of the developmental origins of bone health is critical in the battle against osteoporosis.